Diagnosis easily missed–upper urothelial tumour. Issue 755 (September 1988) - Mufti, G. R.; Virdi, J. S.
Abstract : Four patients with transitional cell tumour of the renal pelvis and ureter who had atypical presentations are described. The associated presenting problem delayed an earlier diagnosis in two patients and facilitated it in the other two.